Native Mycorrhizal Fungi in Land Contaminated Cr, Co and Cu - Muhammad Akhsan Akib; Andi Nuddin; Retno Prayudyaningsih; Syatrawati Syatrawati; Henny Setiawaty (Hasanuddin University, 2019)
Mycorrhizal fungi that are capable of adapting and resistant to heavy metal contaminated environments have received special attention for phytorhizoremediation researchers. The aim of the study was to explore native mycorrhizal fungi from areas contaminated with heavy metals to be used as starter biological agents in the phytorhizoremediation program. This research was carried out in two phases, i.e. rhizosphere sampling of Polypodium glycyrrhiza, Sumasang sp (local name) and Spathoglottis plicata at coordinates 2O31'57,6